IMPROVING THE EFFECTIVENESS OF EXCHANGE RATE POLICY IN CONTEMPORARY VIETNAM - The Dong Phung (Статистика и экономика, 2016)
The article discusses the issue of effectiveness of exchange rate policy in contemporary Vietnam, along with the assessment of the mechanism of this policy from 1989 to the present day. The author analyzes constraints of implementing the exchange rate policy in the past and gives recommendations aimed at improving its efficiency nowadays.